A manipulative use of the word park in names of housing estates - Makuchowska, Marzena (Papers in Linguistics, 2020)
The article describes the currently common phenomenon of using the word park in names of urban facilities, mainly housing estates, for commercial purposes. These names allude to living in favourable conditions, obscuring the fact that their construction is inherently associated with the depletion of green spaces in the city. Development companies transfer to the names of their estates the highly positive associations that a traditionally understood park evokes, thus the first part of the article presents the semantic content of this word. The second part shows how developers justify their names by creating their relationship with the real features of the location or architecture of housing estates, as well as combining the word park with other lexical units with positive connotations. As a consequence, the word park loses its precision and semantic independence, which opens the way to misunderstandings, but also to manipulation and communication violence.